Preparation method and application of conjugated microporous polymer microsphere filler with hollow structure

By polymerizing the conjugated microporous polymer microsphere filler with hollow structure on the surface of silica nanospheres, the thermal insulation and stability of foam materials in the prior art under high temperature and thermal runaway conditions is solved, and efficient thermal insulation and structural stability is achieved, meeting the safety needs of PACK battery packs.

CN119798622APending Publication Date: 2025-04-11ZHUZHOU TIMES NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202510090587.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In existing PACK battery packs, foam materials are difficult to effectively insulate and stabilize in high temperatures and thermal runaway situations, affecting the overall structural stability and safety of the battery pack.

Method used

A conjugated microporous polymer microsphere filler with a hollow structure is used to form a hollow structure by polymerizing 1,3,5-triacetylene benzene and 2,6-dibrom-3-aminopyridine on the surface of silica nanospheres to form a hollow structure, and then etching with hydrofluoric acid to form nano-scale pores to obtain a microsphere filler with excellent thermal insulation and structural stability.

Benefits of technology

The filler has good thermal stability and thermal insulation performance at high temperatures, with a 5% thermal decomposition temperature reaching 376℃. By adding it to the silicone foam material, the thermal insulation and compression performance between the cells is improved, meeting the safety needs of the PACK battery pack at high temperature and thermal runaway conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798622A_ABST
    Figure CN119798622A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a conjugated microporous polymer microsphere filler with a hollow structure, silicon dioxide nanospheres are placed in an organic solvent, after uniform ultrasonic dispersion, 1, 3, 5-triacetylene benzene and 2, 6-dibromo-3-aminopyridine are added, after a catalyst is added, a stirring reaction is carried out in a nitrogen atmosphere to obtain yellow powder, and the yellow powder is dried to obtain the conjugated microporous polymer microsphere filler with the hollow structure. Etching with hydrofluoric acid, cleaning the treated product until the filtrate is transparent and colorless, and drying in vacuum to obtain the conjugated microporous polymer microsphere filler with the hollow structure. Nanoscale holes are formed in the hollow-structure conjugated microporous polymer microsphere filler, so that the hollow-structure conjugated microporous polymer microsphere filler has good heat insulation performance and good heat stability at high temperature, and can be used as a heat-resistant performance enhancing filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silica gel polymer materials, and in particular relates to a preparation method and application of a conjugated microporous polymer microsphere filler with a hollow structure. Background Art

[0002] Silicone rubber is a polymer elastic material with a main molecular chain (-Si-O-Si-) formed by alternating silicon atoms and oxygen atoms. The bond energy of its silicon-oxygen bond is 370 kJ / mol. It has high thermal stability and can be stable at above 200°C for a long time and up to 300°C for a short time. Silicone rubber foam material forms uniform internal pores through foaming, which reduces the density of the material and also gives it excellent intrinsic elasticity.

[0003] The cells in the PACK battery pack are connected in series and parallel, and combined with other electrical systems, thermal management systems, mechanical structures, etc. to form a lithium-ion battery pack. During use, the battery pack must pay close attention to its thermal management, especially thermal runaway management, to ensure stability during service and safety in the event of an accident.

[0004] The battery cells are separated by installing relevant foam materials to ensure that heat is not transferred between the battery cells. Especially when some battery cells have thermal runaway, the impact on adjacent battery cells and the entire battery pack is reduced to meet usage requirements and emergency safety standards.

[0005] Taking into account the vibration reduction requirements of the PACK battery pack during application, the foam material serving between the battery cells needs to have certain compression properties to match the volume changes that occur during the charging and discharging process of the battery cells, so as to ensure that stress relaxation will not occur before the battery pack completes its service, resulting in a decrease in the overall structural stability of the battery pack. Summary of the invention

[0006] In order to overcome the problems in the prior art, the present invention provides a method for preparing a conjugated microporous polymer microsphere filler with a hollow structure and its application. The prepared conjugated microporous polymer microsphere filler with a hollow structure has nanoscale holes inside, has good thermal insulation performance, has good thermal stability at high temperatures, and has a 5% thermal decomposition temperature T d , 5% is 376℃, which can be used as a filler to enhance heat resistance.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: The present invention provides a method for preparing a conjugated microporous polymer microsphere filler with a hollow structure, comprising the following steps: S1. Place silica nanospheres in an organic solvent, disperse them uniformly by ultrasonication, add 1,3,5-triethynylbenzene and 2,6-dibromo-3-aminopyridine, add a catalyst, stir and react under a nitrogen atmosphere to obtain a yellow powder.

[0008] S2. Prepare an aqueous solution containing hydrofluoric acid and an organic solvent, add the solution to the yellow powder obtained in step S1, and allow to stand for treatment.

[0009] S3, washing the product after the standing treatment in step S2 until the filtrate is transparent and colorless, and vacuum drying to obtain a conjugated microporous polymer microsphere filler with a hollow structure.

[0010] In the present invention, 1,3,5-triethynylbenzene and 2,6-dibromo-3-aminopyridine are polymerized on the surface of silica nanospheres. The molecular structure of the chemical reaction is shown below. A large number of aromatic heterocycles in the obtained product structure also give it excellent structural stability. Then, hydrofluoric acid is used to etch away the silica nanospheres. The polymer on the surface serves as a framework to form a hollow structure. Finally, impurities such as monomers, small molecular polymers, and catalysts that may be contained in the powder are washed away to obtain a pure conjugated microporous polymer microsphere filler with a hollow structure.

[0011]

[0012] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, the mass ratio of 1,3,5-triethynylbenzene to 2,6-dibromo-3-aminopyridine is 1:2.2 to 1:2.5.

[0013] In the present invention, the mass ratio of 1,3,5-triethynylbenzene to 2,6-dibromo-3-aminopyridine is controlled within the above range, which can ensure that the reaction is carried out under optimal conditions and prevent the generation of low molecular weight, non-branched by-products.

[0014] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, the stirring reaction temperature is 70 to 90° C., and the reaction time is 36 to 48 hours.

[0015] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, the catalyst is tetrakis(triphenylphosphine)palladium(0) and cuprous iodide.

[0016] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, in step S3, the treated product is washed with chloroform, acetone, deionized water and methanol in sequence.

[0017] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, a flame retardant is added to the transparent colorless filtrate obtained in step S3, and the filler containing the flame retardant is obtained after being dissolved and vacuum dried.

[0018] As an optional embodiment, in the method for preparing polymer microspheres provided by the present invention, the flame retardant is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0019] Based on the same technical features, the present invention also provides the use of the conjugated microporous polymer microsphere filler with a hollow structure prepared by the preparation method of the conjugated microporous polymer microsphere filler with a hollow structure in a silicone foam material for buffering and heat insulation between battery cells.

[0020] As an optional embodiment, in the application provided by the present invention, the silica gel foam material for buffering and heat insulation between battery cells is composed of component A and component B, specifically composed of the following raw materials in parts by weight: Component A: vinyl silicone oil: 20-30; phenyl silicone oil: 5-10; fumed silica: 5-8; hydroxy silicone oil: 1.0-5.0; aluminum hydroxide flame retardant: 10-15; platinum catalyst: 0.1-0.5; hollow conjugated microporous polymer microspheres: 0.4-0.8.

[0021] Component B: vinyl silicone oil: 20-30; phenyl silicone oil: 5-10; hydrogenated silicone oil: 1.0-5.0; fumed silica: 5-8; aluminum hydroxide flame retardant: 10-15; pigment: 0.5-1.0; inhibitor: 0.005-0.01; hollow conjugated microporous polymer microspheres: 0.4-0.8.

[0022] As an optional embodiment, in the application provided by the present invention, the specific surface area of ​​the fumed silica is 100 to 400 m 2 / g.

[0023] As an optional implementation, in the application provided by the present invention, the viscosity of the vinyl silicone oil is 10000-100000 mPa·s, and the mass fraction of vinyl is 0.10-0.40 wt%.

[0024] As an optional embodiment, in the application provided by the present invention, the viscosity of the phenyl silicone oil is 1000 to 5000 mPa·s, and the mass fraction of phenyl is 0.08 to 0.35 wt%.

[0025] As an optional implementation, in the application provided by the present invention, the molar mass fraction of hydroxyl groups in the hydroxy silicone oil is 3.0 to 8.0 wt %.

[0026] As an optional implementation, in the application provided by the present invention, the mass fraction of hydrogen groups in the hydrogen-containing silicone oil is 0.5 to 1.6 wt%.

[0027] As an optional embodiment, in the application provided by the present invention, the inhibitor is one of 1-ethynylcyclohexanol, 3,7,11-trimethyldodecene-3-ol, and 3-methyl-1-dodecene-3-ol.

[0028] As an optional implementation, in the application provided by the present invention, the concentration of the platinum catalyst is 1000-5000 ppm.

[0029] As an optional implementation, in the application provided by the present invention, the particle size of the aluminum hydroxide flame retardant is 5 to 20 μm.

[0030] As an optional embodiment, in the application provided by the present invention, the method for preparing the silica gel foam material for buffering and heat insulation between battery cells comprises the following steps: S1. Add vinyl silicone oil, phenyl silicone oil, fumed silica, hydroxy silicone oil, aluminum hydroxide flame retardant, platinum catalyst and hollow conjugated microporous polymer microspheres into a double planetary mixer according to their mass proportions and mix them evenly.

[0031] S2. Evacuate the double planetary mixer in step S2 to -0.09 to -0.1 MPa, mix evenly and then discharge the material, which is component A.

[0032] S3. Add vinyl silicone oil, phenyl silicone oil, hydrogen silicone oil, fumed silica, aluminum hydroxide flame retardant, pigment, hollow conjugated microporous polymer microspheres and inhibitor into a double planetary mixer according to their mass proportions and mix them evenly.

[0033] S4. Evacuate the double planetary mixer in step S3 to -0.09 to -0.1 MPa, mix evenly and then discharge the mixture to obtain component B.

[0034] S5. Mix component A and component B in equal mass ratio, cure at 50-100°C for 10-15 min, and then perform secondary vulcanization at 150°C for 20 min to obtain a silicone foam material for buffering and heat insulation between battery cells.

[0035] Based on the same technical concept, the present invention also provides the application of the above-mentioned silica gel foam material for buffering and heat insulation between battery cells in battery PACK battery cells.

[0036] Compared with the prior art, the present invention has the following beneficial effects: (1) The hollow conjugated microporous polymer microspheres prepared by the present invention are polymerized from 1,3,5-triethynylbenzene and 2,6-dibromo-3-aminopyridine and have a hollow structure, which gives them excellent thermal insulation performance. At the same time, a large number of aromatic heterocycles in the structure also give them excellent structural stability and good thermal stability at high temperatures. The 5% thermal decomposition temperature T d,5% The temperature of the alloy is 376℃, and it can be used as a filler to enhance heat resistance.

[0037] (2) The silicone foam material for buffering and heat insulation between battery cells provided by the present invention is endowed with good intrinsic heat insulation performance and high temperature resistance by adding synthetic hollow conjugated microporous polymer microspheres. By controlling the addition ratio of hydroxy silicone oil, hydrogen-containing silicone oil and vinyl silicone oil, as well as the catalytic inhibition system, the crosslinking rate is matched with the foaming rate, the foaming and crosslinking are controlled, the pore structure and the hardness of the product are adjusted, and a fine-pore silicone rubber is prepared. The material is endowed with good compression performance, which can meet the application conditions between battery cells in the PACK battery pack and the safety requirements when thermal runaway occurs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 The infrared spectrum test results of the conjugated microporous polymer microspheres with hollow structures prepared in Example 1; Figure 2 The scanning electron microscope test results of the conjugated microporous polymer microspheres with hollow structures prepared in Example 1; Figure 3 The thermogravimetric analysis test results of the conjugated microporous polymer microspheres with hollow structures prepared in Example 1; Figure 4 The infrared spectrum test results of the conjugated microporous polymer microspheres with hollow structures prepared in Example 2; Figure 5 This is the infrared spectrum test result of the conjugated microporous polymer microspheres with hollow structure prepared in Example 3. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0041] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0042] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0043] Example 1 The method for preparing conjugated microporous polymer microspheres with a hollow structure comprises the following steps: (1) Place 1044 mg of silica nanospheres, 30 mL of toluene, and 30 mL of triethylamine in a three-necked flask and disperse them evenly under ultrasonication.

[0044] (2) 240 mg of 1,3,5-triethynylbenzene, 600 mg of 2,6-dibromo-3-aminopyridine, 184 mg of tetrakis(triphenylphosphine)palladium(0), and 15 mg of cuprous iodide were added to the glass reactor of S1.

[0045] (3) The reaction mixture was stirred at 80 °C under nitrogen atmosphere for 48 h to obtain a yellow powder.

[0046] (4) Prepare a mixed solution of 7.5 ml hydrofluoric acid, 20 ml methanol, and 15 ml deionized water.

[0047] (5) The product of (3) is placed in the product of (4) and allowed to stand for 6 hours.

[0048] (6) The product of (5) was washed with chloroform, acetone, deionized water and methanol until the filtrate was transparent and colorless.

[0049] (7) Place 5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 15 ml of ethanol in a conical flask.

[0050] (8) Stir (7) at 50 °C until DOPO is completely dissolved in ethanol.

[0051] (9) The product of (6) is added to the product of (8), and the mixture is placed in a vacuum oven for 4 hours to obtain conjugated microporous polymer microspheres with a hollow structure.

[0052] In order to characterize the hollow structure conjugated microporous polymer microspheres synthesized in Implementation 1, infrared spectroscopy was performed on them. The results are as follows: Figure 1 As shown, 3500 ~3000 The absorption peak between the two groups is -NH2, indicating that the halogenated monomer is successfully combined with 1,3,5-triacylbenzene; the substituted benzene aromatic hydrocarbon CAr -H stretching vibration at 2930 The characteristic peak appeared at 1631. ~1000 In the range, the vibration peak of Si-O-Si is at 1060 In addition, the infrared spectrum at 887 ,809 and 703 There are multiple peaks at the benzene ring trisubstituted C Ar The -H bending vibration corresponds to the presence of 1,3,5-triethynylbenzene.

[0053] In order to characterize the porous structure of the hollow conjugated microporous polymer microspheres, scanning electron microscopy was performed on them. The results are as follows Figure 2 As shown, the synthesized polymer is in the form of obvious microspheres with nano-scale pores inside, making it an ideal thermal insulation filler.

[0054] In order to characterize the thermal stability of the hollow structured conjugated microporous polymer microspheres, a thermogravimetric analysis test was performed. The results are shown in Figure 3. The synthesized polymer has good thermal stability at high temperatures, and the 5% thermal decomposition temperature T d,5% The temperature of the alloy is 376℃, and it can be used as a filler to enhance heat resistance.

[0055] Example 2 The difference from Example 1 is that 1,3,5-triethynylbenzene is 240 mg, 2,6-dibromo-3-aminopyridine is 552 mg, and the remaining steps are the same as in Example 1. The product prepared in Example 2 was tested by infrared spectroscopy, and the results are as follows: Figure 4 shown.

[0056] Example 3 The difference from Example 1 is that 1,3,5-triethynylbenzene is 240 mg, 2,6-dibromo-3-aminopyridine is 576 mg, and the remaining steps are the same as in Example 1. The product prepared in Example 3 was tested by infrared spectroscopy, and the results are as follows: Figure 5 shown.

[0057] Example 4 A method for preparing a silica gel foam material for buffering and heat insulation between battery cells comprises the following steps: 20000mPa.s vinyl silicone oil (24g), 2000mPa.s phenyl silicone oil (5g), 100mPa.s 2 / g specific surface area fumed silica (6 g), 5wt% hydroxy silicone oil (2.2 g), 10μm aluminum hydroxide flame retardant (12 g), 2000ppm platinum catalyst (0.3 g) and hollow conjugated microporous polymer microspheres (0.5 g) prepared in Example 1 were added into a double planetary mixer and uniformly mixed for 20 min to obtain component A; 20000mPa.s vinyl silicone oil (24.5 g), 2000mPa.s phenyl silicone oil (5 g), 0.8wt% hydrogenated silicone oil (1.0 g), 100mPa.s 2 / g specific surface area fumed silica (6g), 10μm aluminum hydroxide flame retardant (12g), pigment (0.5g), hollow conjugated microporous polymer microspheres prepared in Example 1 (0.5g) and 1-ethynyl cyclohexanol (0.5g) were added to a double planetary mixer and uniformly mixed for 20 minutes to obtain component B. Components A and B were mixed in equal mass, calendered, cured in an oven at 85°C for 12min, and then vulcanized in an oven at 150°C for 20min to obtain a silica gel foam material for buffering and heat insulation between battery cells. The performance test results are shown in Table 1.

[0058] Example 5 A method for preparing a silica gel foam material for buffering and heat insulation between battery cells comprises the following steps: 50000mPa.s vinyl silicone oil (24g), 2000mPa.s phenyl silicone oil (5g), 200mPa.s 2 / g specific surface area fumed silica (6 g), 6 wt% hydroxy silicone oil (2.2 g), 15 μm aluminum hydroxide flame retardant (12 g), 2000 ppm platinum catalyst (0.3 g) and hollow conjugated microporous polymer microspheres prepared in Example 2 (0.5 g) were added into a double planetary mixer and uniformly mixed for 20 min to obtain component A; 50000 mPa.s vinyl silicone oil (24.5 g), 2000 mPa.s phenyl silicone oil (5 g), 0.8 wt% hydrogenated silicone oil (1.0 g), 100 mPa.s 2 / g specific surface area fumed silica (6g), 15μm aluminum hydroxide flame retardant (12g), pigment (0.5g), hollow conjugated microporous polymer microspheres prepared in Example 2 (0.5g) and 1-ethynyl cyclohexanol (0.5g) were added to a double planetary mixer and uniformly mixed for 20 minutes to obtain component B. Components A and B were mixed in equal mass, calendered, cured in an oven at 85°C for 12min, and then vulcanized in an oven at 150°C for 20min to obtain a silica gel foam material for buffering and heat insulation between battery cells. The performance test results are shown in Table 1.

[0059] Example 6 A method for preparing a silica gel foam material for buffering and heat insulation between battery cells comprises the following steps: 10000mPa.s vinyl silicone oil (24g), 2000mPa.s phenyl silicone oil (5g), 200mPa.s 2 / g specific surface area fumed silica (6 g), 6 wt% hydroxy silicone oil (2.2 g), 15 μm aluminum hydroxide flame retardant (12 g), 2000 ppm platinum catalyst (0.3 g) and hollow conjugated microporous polymer microspheres (0.5 g) prepared in Example 3 were added into a double planetary mixer and uniformly mixed for 20 min to obtain component A; 10000 mPa.s vinyl silicone oil (24.5 g), 2000 mPa.s phenyl silicone oil (5 g), 0.8 wt% hydrogenated silicone oil (1.0 g), 100 mPa.s 2 / g specific surface area fumed silica (6g), 15μm aluminum hydroxide flame retardant (12g), pigment (0.5g), hollow conjugated microporous polymer microspheres prepared in Example 3 (0.5g) and 1-ethynyl cyclohexanol (0.5g) were added to a double planetary mixer and uniformly mixed for 20 minutes to obtain component B. Components A and B were mixed in equal mass, calendered, cured in an oven at 85°C for 12min, and then vulcanized in an oven at 150°C for 20min to obtain a silica gel foam material for buffering and heat insulation between battery cells. The performance test results are shown in Table 1.

[0060] Comparative Example The difference from Example 4 is that in the comparative example, no polymer microsphere filler is added.

[0061] 20000mPa.s vinyl silicone oil (24.5g), 2000mPa.s phenyl silicone oil (5g), 100mPa.s 2 / g specific surface area fumed silica (6g), 5wt% hydroxy silicone oil (2.2g), 10μm aluminum hydroxide flame retardant (12g), and 2000ppm platinum catalyst (0.3g) were added into a double planetary mixer and mixed evenly for 20 min to obtain component A; 20000mpa.s vinyl silicone oil (25g), 2000mpa.s phenyl silicone oil (5g), 0.8wt% hydrogenated silicone oil (1.0g), 100m 2 / g specific surface area fumed silica (6g), 10μm aluminum hydroxide flame retardant (12g), pigment (0.5g) and 1-ethynyl cyclohexanol (0.5g) were added to a double planetary mixer and uniformly mixed for 20 minutes to obtain component B. Components A and B were mixed in equal mass, calendered, cured in an oven at 85°C for 12min, and then vulcanized in an oven at 150°C for 20min. The performance test results are shown in Table 1.

[0062] The performance test results of the silica gel foam materials for buffering and heat insulation between battery cells prepared in Examples 4 to 6 and the comparative example are shown in Table 1 below.

[0063] Table 1: Performance test of silica gel foam material for buffering and heat insulation between battery cells in Examples 4 to 6 and Comparative Examples

[0064] It can be seen from Table 1 that this embodiment has good compression performance, heat resistance and thermal insulation performance, and is non-toxic and harmless to the environment; at the same time, compared with the comparative example, the thermal insulation performance of each embodiment is significantly improved.

[0065] The present invention adopts a calendering preparation process, and the prepared silica gel foam material for buffering and heat insulation between battery cells has uniform overall cross-linking and uniform pore distribution, a high degree of automation in the production process, and is suitable for large-scale production.

[0066] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing a conjugated microporous polymer microsphere filler with a hollow structure, characterized in that: The following steps are involved: S1, placing silica nanospheres in an organic solvent, uniformly dispersing them by ultrasonication, adding 1,3,5-triethynylbenzene and 2,6-dibromo-3-aminopyridine, adding a catalyst, stirring and reacting under a nitrogen atmosphere to obtain a yellow powder; S2, prepare an aqueous solution containing hydrofluoric acid and an organic solvent, add it to the yellow powder obtained in step S1, and let it stand for treatment; S3, washing the product after the standing treatment in step S2 until the filtrate is transparent and colorless, and vacuum drying to obtain a conjugated microporous polymer microsphere filler with a hollow structure.

2. The method for preparing the conjugated microporous polymer microsphere filler with a hollow structure according to claim 1, characterized in that: The mass ratio of the 1,3,5-triethynylbenzene to 2,6-dibromo-3-aminopyridine is 1:2.2 to 1:2.

5.

3. The method for preparing the conjugated microporous polymer microsphere filler with a hollow structure according to claim 1, characterized in that: In step S1, the stirring reaction temperature is 70-90° C., and the reaction time is 36-48 h.

4. The method for preparing the conjugated microporous polymer microsphere filler with a hollow structure according to claim 1, characterized in that: In step S1, the catalyst is tetrakis(triphenylphosphine)palladium(0) and cuprous iodide.

5. The method for preparing the conjugated microporous polymer microsphere filler with a hollow structure according to claim 1, characterized in that: In step S3, the treated product is washed with chloroform, acetone, deionized water and methanol in sequence.

6. The method for preparing the conjugated microporous polymer microsphere filler with a hollow structure according to claim 1, characterized in that: The flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added to the transparent colorless filtrate obtained in step S3, dissolved and then vacuum dried to obtain a filler containing the flame retardant.

7. Use of the conjugated microporous polymer microsphere filler with a hollow structure prepared by the method for preparing the conjugated microporous polymer microsphere filler with a hollow structure as claimed in any one of claims 1 to 6 in a silica gel foam material for buffering and heat insulation between battery cells.

8. The use according to claim 7, characterized in that: The silica gel foam material for buffering and heat insulation between battery cells is composed of component A and component B, and specifically consists of the following raw materials in parts by weight: Component A: vinyl silicone oil: 20-30; phenyl silicone oil: 5-10; fumed silica: 5-8; hydroxy silicone oil: 1.0-5.0; aluminum hydroxide flame retardant: 10-15; platinum catalyst: 0.1-0.5; hollow conjugated microporous polymer microspheres: 0.4-0.8; Component B: vinyl silicone oil: 20-30; phenyl silicone oil: 5-10; hydrogenated silicone oil: 1.0-5.0; fumed silica: 5-8; aluminum hydroxide flame retardant: 10-15; pigment: 0.5-1.0; inhibitor: 0.005-0.01; hollow conjugated microporous polymer microspheres: 0.4-0.

8.

9. The use according to claim 7, characterized in that: The specific surface area of ​​the fumed silica is 100 to 400 m 2 / g; the viscosity of the vinyl silicone oil is 10000-100000 mPa·s, and the mass fraction of vinyl is 0.10-0.40 wt%; the viscosity of the phenyl silicone oil is 1000-5000 mPa·s, and the mass fraction of phenyl is 0.08-0.35 wt%; the molar mass fraction of hydroxyl groups in the hydroxy silicone oil is 3.0-8.0 wt%; the mass fraction of hydrogen groups in the hydrogen-containing silicone oil is 0.5-1.6 wt%; the inhibitor is one of 1-ethynylcyclohexanol, 3,7,11-trimethyldodecene-3-ol, and 3-methyl-1-dodecene-3-ol; the concentration of the platinum catalyst is 1000-5000 ppm; and the particle size of the aluminum hydroxide flame retardant is 5-20 μm.

10. The use according to claim 7, characterized in that: The preparation method of the silica gel foam material for buffering and heat insulation between battery cells comprises the following steps: S1. Add vinyl silicone oil, phenyl silicone oil, fumed silica, hydroxy silicone oil, aluminum hydroxide flame retardant, platinum catalyst and hollow conjugated microporous polymer microspheres into a double planetary mixer according to their mass proportions and mix them evenly; S2, evacuate the double planetary mixer in step S2 to -0.09 to -0.1 MPa, mix evenly and then discharge the material, which is component A; S3, adding vinyl silicone oil, phenyl silicone oil, hydrogen silicone oil, fumed silica, aluminum hydroxide flame retardant, pigment, hollow conjugated microporous polymer microspheres and inhibitor into a double planetary mixer according to mass proportions, and mixing evenly; S4, evacuate the double planetary mixer in step S3 to -0.09 to -0.1 MPa, mix evenly and then discharge the material to obtain component B; S5. Mix component A and component B in equal mass ratio, cure at 50-100°C for 12-15 min, and then perform two-stage vulcanization at 150°C for 20 min to obtain a silicone foam material for buffering and heat insulation between battery cells.

Citation Information

Cited By

  • Amphiphilic polymer as well as preparation method and application thereof

    CN120518870A

  • Amphiphilic polymers, methods of making and using the same

    CN120518870B

  • Heat insulation fabric and preparation method thereof

    CN120738791A

  • Thermal insulation fabric and method of making same

    CN120738791B